To what extent does South Africa's legal framework offer adequate protection to victims of non-consensual pornography? - Van Der Spuy, Lara (Department of Public Law, 2025)
This dissertation aims to analyse to what extent the South African legal framework offers adequate protection to victims of non-consensual pornography. Non-consensual pornography, understood as the unlawful distribution of intimate content without a person's consent, has gained popularity on the internet. This new form of cybercrime has posed challenges to lawmakers who have struggled to write legislation that could effectively combat it. Clear and effective laws against this offence are crucial in protecting victims and also their right to privacy and sexual autonomy. In South Africa two primary pieces of legislation deal with non-consensual pornography, the Films and Publications Amendment Act and the Cybercrimes Act. There are various non-criminal remedies available, such as initiating a civil claim for damages through the Protection of Personal Information Act 4 of 2013, but I argue that the harm caused by non-consensual pornography requires the maximum deterrence in the criminal law. This research aims to analyse the effectiveness of the South African legislation available to victims, and identify gaps that could be improved.